PEMBUATAN PROGRAM APLIKASI INVENTORY BERBASIS DESKTOP MENGGUNAKAN VISUAL BASIC.NET - didik - warasto (JSIK (Jurnal Sistem Informasi Kaputama), 2023)
"Data-Processing of  Package Delivery In PT. MAJI - Salatiga  use the programming language visual basic 6.0. with the progress of information technology in this time computer play a part very important in the world of job. In technological growth this computer can assist the us in producing and to save information in a complex system information.   In general computer used for the hollowing of duty like typing, but in fact knowledge about computer need more developing so that can overcome the problems which complex progressively.   As for one of example of problems able to be overcome with the computer peripheral that is problems of delivery of goods package that happened in PT. MAJI - Salatiga    By using programming language of visual basic 06, in this paper writer hope can assist the PT. MAJI - Salatiga    in solving problems of delivery of goods package especially, so that will get the data and report which quickly, precisely and accurate. By using input of scrip certificate transaction, town data, data of tariff of package and transaction claim so that can complete the process which have there.